Tinjauan Yuridis Perbuatan Percobaan Untuk Melakukan Tindak Pidana Teorisme Menurut Undang-Undang Nomor 5 Tahun 2018 (Analisis Putusan Nomor 13/Pid.Sus/2020/PN.Jkt.Tim) - Jasaraharja Sembiring (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2022)
Terrorism is not just an act of terror, but in fact the criminal act of terrorism also violates human rights as basic rights inherent in human nature, namely the right to live and the right to feel safe and comfortable. The formulation of the problem in this thesis is how to apply criminal sanctions to criminal acts of attempted terrorism, how to impose criminal sanctions against perpetrators of attempted criminal acts of terrorism in Decision Number 13/Pid.Sus/2020/PN.Jkt.Tim, how are legal considerations? judges in Decision Number 13/Pid.Sus/2020/PN.Jkt.Tim against attempted acts of terrorism. The results of the study indicate that the application of criminal sanctions to criminal acts of attempted terrorism is regulated in Article 15 in conjunction with Article 7 of Law Number 15 of 2003 concerning Eradication of Criminal Acts of Terrorism jo. Law Number 5 of 2018 concerning Amendments to Law of the Republic of Indonesia Number 15 of 2003 that the defendant has been proven to have committed a criminal act of terrorism, as charged by the public prosecutor. The imposition of criminal sanctions against the perpetrators of the criminal act of attempted terrorism in Decision Number 13/Pid.Sus/2020/PN.Jkt.Tim is the defendant Musyafir Alias One Alias Kusman who has been legally and convincingly proven guilty of committing a criminal act of trial to commit a criminal act of terrorism sentenced to imprisonment for 4 (four) years Keywords: Experiment, Crime, Theorism